CONSTITUTIONAL INTERPRETATION OF ORIGINAL INTENT ON FINDING THE MEANING OF SOCIAL JUSTICE IN THE CONSTITUTIONAL REVIEW - Agnes Harvelian; Muchamad Ali Safa'at; Aan Eko Widiarto; Indah Dwi Qurbani (Yustisia Jurnal Hukum, 2020)
This article will study whether original intent method able to find justice in constitution and formulate constitutional interpretation that will able to perform constitutional supremacy. This study uses a doctrinal approach or also referred to as the normative legal approach. The method taken in this writing is analysis descriptive which describes and analyses constitutional interpretation with original intent method. Formulating constitution interpretation which answers people dynamic but doesn’t lose its original constitutional intent. This research shows that Constitutional interpretation with original intent method can mean as an interpretation which assimilate the spirit of how the original written constitution was formulated when building UUD 1945, the opinion of constitution’s founders in their understanding on the purpose and the nation’s ground principals. Basically, All the rules must not contradict with constitution’s intention. The freedom of judges to decide is not freedom without limits. The limitations of judges' freedom of interpretation are Pancasila and the 1945 Constitution. Decisions made by judges must not conflict with Pancasila and the 1945 Constitution, constitutional judges have great power in interpreting the 1945 Constitution. This power is vulnerable to various interests which make the decisions of constitutional judges not objective. Accountability of decisions in public and academics should be a legal idea that can be realized, not to judge the verdict but to know the basis of interpretation and or legal discovery by constitutional judges